The Role of the PUK Peshmerga Forces in Protecting the National Identity during the Anfal Process The First Phase - Muhammad, D.Zana Faqe (Sulaimani Journal for Humanities, 2025)
Anfal was a planned military campaign by the Iraqi government to destroy Kurdish identity and the Kurdish liberation movement in Kurdistan, especially after the resumption of the armed struggle led by the Patriotic Union of Kurdistan in 1975, where the PUK peshmerga forces were able to liberate a large part of the southern Kurdistan. Therefore, the Iraqi government began the crime of Anfal on February 23, 1988, and ended it on September 6 of the same year. It was implemented in eight phases in six different regions. The first phase of this campaign began with the attack on the Jafayati Valley on February 23, 1988, where the PUK leadership headquarters was located. To prevent the destruction of the areas and protect the lives and identity of the population, the PUK peshmerga forces have clashed with the Iraqi army forces, where several people on both sides were killed. This study consists of an introduction, two independent sections, conclusions, a reference list, and an appendix of documents. The first section, entitled “Anfal: Phase One”, explains the reasons and how the Iraqi government launched the plan for Anfal in the Jafayati Valley. In the second section, entitled “The Role of the PUK Peshmerga Forces in protecting the National Identity during the Anfal Process: Phase One”, we discussed the role of the PUK Peshmerga Forces in planning and mapping to face the Iraqi army forces to protect the area and national identity, and tried to determine the number of dead on both sides.
Keywords: Anfal; Iraqi Army; Peshmerga Forces; Jafayati Valley; Encounter; Killed